BUKTI-BUKTI FONOLOGIS PEMBEDA BAHASA WANOKAKA DAN BAHASA ANAKALANG DI SUMBA TENGAH-NTT - Budasi, I Gede (Universitas Pendidikan Ganesha, 2010)
Wanokaka (Wn) and Anakalang (An) languages are two of the seven languages spoken in Sumba, East NusaTenggara (Budasi, 2007). The speakers of the two languages live in Mid Sumba Regency within East NusaTenggara Province. Some linguists consider the two are dialects of Sumba language ( All isolects spoken inthe island are considered as one language). In Budasi (2007, 2009), however, Wn and An were quantitativelyproved as two different languages spoken in the regency. Based on the lexicostatistic analysis and Swadesh’sclassification of language, the relatedness of the two languages was 75.5 %, which means that their subgroupingrelationship belongs to language family (They are in two different laguage relationship, but not intwo-dialect relationship of the same family). In Budasi (2007), both languages were hyphotesized originallyfrom Proto WN-An in Sumba Group of Languages. Based on this hyphothesis, this paper aims at describingqualitatively the phonological evidences which differentiate the two different languages of the same family.In this study, the comparative method was applied. The population of the study comprised the speakers ofthe two languages. Three informant samples were selected based on a set of criteria. The instruments of thedata gathering were three word lists: Swadesh, Nothofer, and Holle; and a tape recorder. Two types of data,secondary and primary, were collected. The obtained data were analysed descriptively and qualitattively.This study concluded that qualitatively, Wn and An were two different languages of the same family underSumba Gropup of Languges. The qualitative evidences were as follows: a) the phonological evidences whichdiffered Wn and An, that is, vocal phonemes PWn-An *a dan *e in penultima and antepenultima positionsretained in An; however, in Wn they innovated ›vowel cluster Wn e-a ; b) unidentical vowel cluster PWn-An*a-u was in correspondence with the unidentical vowel cluster Wn o-u and An a-u; PWn-An *a-u innovatedinto Wn o-u while in An it retained; c) unidentical vowel cluster PWn-An *a-i was in correspondence withthe unidentical vowel cluster Wn e-i and An a-i, which innovated in Wn to become Wn e-i, while in Anretained.Unidentical vowel cluster PWn-An *a-i retained in An; however, it innovated in Wn o. It formed secondarychange, that is, highering central vocal phoneme PWn-An *a ›a central back phoneme Wn o, while in An itretained. The whole evidences, then, confirm the quantitative data findings mentioned in Budasi (2007, thatis, Wn and An were two different languages which were generated directly from the Proto Wn-An underSumba Group of Languages.Key words: lexicostatistics, language family, and comparative method.